(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2024)
Triage, i.e. the method of setting priorities for the selection of patients for treatment, from a larger group of needy people, has always raised several moral dilemmas. However, the issue has returned to the center of bioethics debate, because of the problems which have arisen out of the Covid-19 pandemic. After a quick historical introduction, this article will address the topic of triage starting from the SIAARTI Recommendations of 6 March 2020, which animated the debate on the different ethical perspectives related to scarce resources allocation. Furthermore, it will focus on the Opinion of the Italian Committee for Bioethics released on 8 April 2020 on the issue of the barriers to healthcare access encountered by patients in conditions of resource shortage, and on the Recommendations jointly issued by SIAARTI and SIMLA on 13 January 2021. Finally, the article will put forward some proposals on the criteria for allocating scarce resources.